Guided Inquiry with STEAM: Fostering Critical Thinking on Fluid Statics Concepts - Prima Warta Santhalia; Diane Noviandini (Postgraduate, University of Mataram, 2026)
Critical thinking is one of the higher levels of thinking. This study aims to determine the level of critical thinking of students using the STEAM-integrated guided inquiry learning model on static fluid material. The research method used is mixed methods that focuses on the design of embedded experimental models. The subjects in this study consisted of 11th grade high school students in Salatiga. Data from this study were analyzed quantitatively and qualitatively. The conclusion of this study is that there is an increase before and after being taught using STEAM-integrated guided inquiry learning. This is evidenced by the results of the analysis of students' critical thinking levels which were previously in the good category of 3.12%, moderate 31.25%, poor 28.12%, and very poor 37.5% and after learning using STEAM-integrated guided inquiry learning are in the very good, good, and moderate categories. The percentages are very good 6.25%, good 53.12%, and moderate 40.62%.